2018
DOI: 10.1080/19768354.2018.1525429
|View full text |Cite
|
Sign up to set email alerts
|

BRG1 Promotes chromatin remodeling around DNA damage sites

Abstract: Chromatin remodeling complexes play important roles in various DNA metabolism processes, including DNA damage repair. BRG1 is the core subunit of the SWI/SNF complex, which plays critical roles in cell cycle regulation, cell development, cell differentiation, and tumorigenesis. In the present study, we report that BRG1 depletion increased the percentage of apoptotic cells in etoposide-treated cells. Moreover, western blotting and immunofluorescence data showed that BRG1 depletion decreased H2AX phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…3a , orange trace), indicating that BET proteins play a role in remodeling chromatin at DSBs. Brahma-Related Gene 1 (BRG1) is an ATPase subunit of the SWI/SNF chromatin remodeling complex, and has been linked to both DNA repair 51 53 and BET proteins 54 , 55 . To test whether BET proteins regulate binding of BRG1 during DSB repair, DNA-bound proteins were analyzed by plasmid pull-down.…”
Section: Resultsmentioning
confidence: 99%
“…3a , orange trace), indicating that BET proteins play a role in remodeling chromatin at DSBs. Brahma-Related Gene 1 (BRG1) is an ATPase subunit of the SWI/SNF chromatin remodeling complex, and has been linked to both DNA repair 51 53 and BET proteins 54 , 55 . To test whether BET proteins regulate binding of BRG1 during DSB repair, DNA-bound proteins were analyzed by plasmid pull-down.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to transcription, BRG1 also has roles in DNA processes which further contribute to its importance in cancer [13][14][15]. BRG1 has been shown to promote DNA repair at doublestranded breaks through nucleosome repositioning and recruitment of repair factors [13][14][15], whilst its absence has been demonstrated to induce replication stress which is a major cause of genome instability [16,17]. The associations between BRG1 and cancer, and the types of genetic alterations that are observed are highly dependent on the cancer type.…”
Section: Smarca4 As An Epigenetic Regulator In Cancermentioning
confidence: 99%
“…Qi et al [56,57] found that BRG1 decreases the nucleosomes stability at DSBs and creates an open and relaxed chromatin structure in SW13 and U2OS cells. It shows that BRG1 is crucial in early damage repair by remodeling the chromatin structure near DNA damage sites.…”
Section: Chromatin Modifications In Dsb Repairmentioning
confidence: 99%